The association of crevicular albumin level with the severity of periodontal destruction in chronic periodontitis patients after initial periodontal treatment - Fadhil, Raghad (Journal of Baghdad College of Dentistry, 2014)
Background: Gingival crevice fluid (GCF) is a mixture of substances derived from serum, leukocytes, and structural cells of periodontium and oral bacteria. These substances possess a great potential for serving as indicators of periodontal disease and healing after therapy the main purpose of this study was to find if there is a difference in albumin concentration between healthy and diseased periodontal tissues and to compare between diseased group according to pocket depth Materials and methods: total sample composed of 60 pockets found in 35 patients all of them had no history of any systemic disease, The samples were divided in to three main group that include two diseased groups divided according to the depth of the periodontal pocket (group I were the pocket depth less than 6mm and group II were the pocket depth is equal or more than 6mm) and one healthy group (group III). Sampling of GCF were taken from patients in the second visits of periodontal treatment A previously weighed strips of filter paper size 30 were gently inserted in to the selected pocket depth until resistance was felt the filter paper left in place for 30 seconds and after removal they were weighed on a chemical balance. The difference between the weights of filter paper before and after absorption of exudates was calculated and each filter strips was placed in a tube containing o.3ml of normal saline then transferred and stored at -20C.on the day of analysis the samples were centrifuged at 10.000rpm for 20 minutes .the supernatant was used for assessment of Albunim colorimetrically similar to that of blood. Results: Comparison for gingival fluid weight were shown a non significant difference in the weight between group I&II at a P values >0.05 while there were a highly significant difference between group I&III and between group II&III at P values 0.05 intra groups correlation between albumin content in gingival fluid and periodontal parameter there were a significant negative correlation between plaque index and albumin in group I and II while anon significant correlation in group III also a significant and highly significant correlation were found between albumin and weight of gingival fluid in group I and II while anon significant differences in group III as shown in the table while there were anon significant differences between albumin content of gingival fluid and the gingival index, probing pocket depth and clinical attachment loss. Conclusion: the gingival crevicular fluid is an aqueous component in which is true trasudate and inflammatory exudates after the initial periodontal treatment in which it increased in weight as the inflammation present but the concentration of albumin may became a no significantly different compared with clinically healthy gingiva. As the initial periodontal treatment took place for each patients.